Building information modeling for airports - McCuen, Tamera L. (Tamera Lee), 1964-; Pittenger, Dominique M. (Dominique Michelle), 1975-; National Research Council (U.S.). Transportation Research Board; Airport Cooperative Research Program; United States. Federal Aviation Administration (Washington, D.C. : Transportation Research Board, 2016)
TRB's Airport Cooperative Research Program (ACRP) Synthesis 70: Building Information Modeling for Airports summarizes current state of the art and practice for Building Information Modeling (BIM). BIM is a digital representation of a facility's physical and functional characteristics. BIM offers tools that allow airport decision makers to understand all components of a facility--their location, and their attributes, both graphically and systematically--to minimize the total cost of owning and operating an airport facility. The report provides a snapshot of experiences related to the emergence of BIM in North American airports
At head of title: Airport Cooperative Research Program
Includes bibliographical references (pages 45-47)
Keywords: Building information modeling -- North America; Airports -- North America -- Management; Airports -- North America -- Management -- Data processing